Current Concepts in Tourniquets - Jeyasurya, Jeswin; Jameson, Michael; Glinz, Ken; Sadr, Hooman; Day, Brian; Masri, Bassam; McEwen, James (CMBES Proceedings, 2014)
Pneumatic tourniquets are used many thousands of times per day in orthopaedic and non-orthopaedic surgical procedures throughout the world, facilitating operations by reliably establishing a bloodless surgical field with a high level of safety. Within the last thirty years, there have been important improvements in the technology of tourniquet instruments and tourniquet cuffs, leading to greater safety and efficacy in surgical procedures and non-surgical settings. This paper provides an overview of current concepts in tourniquets in the following six areas: 1) Safety features integrated into modern tourniquet systems; 2) The use of Limb Occlusion Pressure (LOP) to enable individualized, optimal tourniquet pressure settings to be achieved; 3) Personalization of tourniquet cuffs through the use of variable contour design and availability of cuffs to fit pediatric and bariatric patient populations; 4) Reduction of soft tissue injuries through the use of limb protection sleeves matched to the limb size and cuff size; 5) Non-pneumatic tourniquets, developed for stopping arterial blood flow simply and rapidly in pre-hospital military and emergency settings, but with less safety and less accuracy than surgical tourniquet systems; and 6) Ongoing innovations to automatically maintain tourniquet pressures near ongoing optimal limb occlusion pressure for individual patients throughout a surgical procedure.